Implementasi Pendidikan Karakter Melalui Pengelolaan Kelas yang Dinamis di SD Muhammadiyah 5 Surakarta Tahun Ajaran 2015/2016 - Panuntun, Yunus Bagus, Drs. Saring Marsudi, SH. M.Pd (2016)
Yunus Bagus Panuntun/A510120045. IMPLEMENTATION OF CHARACTER EDUCATION THROUGH THE DYNAMIC MANAGEMENT CLASS IN SD MUHAMMADIYAH 5 SURAKARTA ACADEMIC YEAR 2015/2016. Essay. The Faculty of Education, University of Muhammadiyah Surakara. March, 2016. This research aims to: 1) Know the teachers' understanding of character education in SD Muhammadiyah 5 Surakarta 2) Describe the implementation of character education through the management of dynamic classes in SD Muhammadiyah 5 Surakarta 3) Describe the character values instilled through the management of dynamic classes in SD Muhammadiyah 5 Surakarta 4) Describe the constraints experienced teachers in the implementation of character education through dynamic classroom management in SD Muhammadiyah 5 Surakarta 5) Describe the solution in the cultivation of character values through dynamic classroom management in SD Muhammadiyah 5 Surakarta. This type of research is qualitative research) with case study research design. The informants are teachers and learners low grade. Data collection techniques used were observation, interviews, documentation, and field notes. Data were analyzed through the steps of data reduction and conclusion. Mechanical data validity checking is done by triangulation of sources and methods. The results showed that the management measures dynamic classes such as conducting social analysis, setting the seat position, resolve discipline problems, use the library, and to activate the whiteboard can shape the values of religious character, discipline, friendship, love reading, caring environment, independent, and curiosity of learners. This study therefore concluded that the implementation of character education through dynamic classroom management can shape character values in the lower grade students of SD Muhammadiyah 5 Surakarta academic year 2015/2016. Keywords: character, character education, dynamic classroom management